The relationship among the unemployment rate, inflation and child abuse rate in Malaysia - Mohd Shahidan, Shaari (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2016)
Link to publisher's homepage at http://ijbt.unimap.edu.my